Development of a novel in vitro method for drug development for fish; application to test efficacy of antimicrosporidian compounds. (6th December 2014) - Saleh, M.; Kumar, G.; Abdel‐Baki, A‐A.; Dkhil, M.; El‐Matbouli, M.; Al‐Quraishy, S.
Abstract : Few drugs are approved for treating diseases caused by parasites in minor species such as fish. This is due, in part, to the expense of drug development and to the comparatively small market. In vivo effectiveness trials for antiparasitic drugs are costly, time consuming and require ethics approval, therefore an in vitro screening approach is a cost‐effective alternative to finding promising drug candidates. We developed an in vitro testing system to test antimicrosporidial compounds against a microsporidian pathogen Heterosporis saurida . Five antiparasitic compounds, albendazole, fumagillin, TNP‐70, nitazoxanide and lufenuron, were assayed for antimicrosporidial activity. All compounds reduced the number of H saurida spores in infected cells when applied at a concentration that did not appear to be toxic to the host cells. Albendazole inhibited replication of H saurida by >60 per cent, fumagillin and its analogue TNP‐470 inhibited H saurida >80 per cent, nitazoxanide and lufenuron inhibited growth >70 per cent. The data suggest that both fumagillin and its analogous TNP‐70 hold the best promise as therapeutic agents against H saurida. The ability to use fish cell cultures to assess drugs against H saurida demonstrates an approach that may be helpful to evaluate other drugs on different microsporidia and host cells.